Assessing Students’ Strategic Competence in Speaking English - TERESHCHUK, Diana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article proposes criteria for testing university students’ strategic competencyin speaking. The roots of the derivation of the four criteria and their indicatorsis the demands for the future specialists – university students, the essenceand distinctive peculiarities of strategic competence, the specificity of speakingas a skill and as an activity, the modern tendencies in evaluation processes.Hence, such criteria with the corresponding indicators for evaluation were established:cognitive, communicative, goal-seeking, educational-compensatory.Studying specific tasks for assessment and developing tools of evaluating strategiccompetence in writing and interaction activities open new prospects forfurther educational research.